(untitled) (e-Journal of Linguistics, 2023)
Transitivity is one of the syntactical studies that is affected by morphology. This article describes how transitivity is expressed and how transitive are the verbs in the constructions of clauses in the Bima Language. Transitivity in the Bima Language is mostly expressed using basic verbs which can be syntactically used as verbs in clauses. Apart from this, prefix ka- with its variant ca- is used to derive transitive from intransitive verbs and nonverbal categories. Meanwhile, particle kai and wea are used to derive ditransitive from transitive verbs. The transitivity of verbs in the Bima Language varies from one to another. Whether the verbs are said to have high or low transitive, it depends on how they fulfill the transitive parameter (Hooper and Thompson, 1989). Form 10 parameters of transitivity, there are four parameters which fit the Bima Language transitivity, such as participant (agents and patients), affectedness of patient, potency of agent, and volitionality. The constructions which are considered as high transitive is that if the constructions use action verbs rather than state verbs and mental verbs. It is found out that action verbs can cause the agents of the clause to take control on the activities, can affect the patients, and intensively can cause the agent to do the activities expressed by the verbs deliberately and intensively.